Penggunaan Media Puzzle untuk Meningkatkan Literasi Membaca Siswa Kelas 3 di MI Al-Barokah Ajung Jember - Siti Amanda; Muhammad Suwignyo Prayogo; Aprilia Yuliantika; Maimunah Maimunah (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This study has two main objectives, namely (1) to identify various difficulties experienced by students in reading activities in class III of MI Al-Barokah, and (2) to analyze the application of puzzle media as an alternative solution to overcome these difficulties. The research approach used is qualitative with a case study method. Data collection was carried out through observation, interviews, and documentation of teaching and learning activities. Data analysis followed the Miles and Huberman model, which includes the stages of data collection, data presentation, and conclusion drawing. The results showed that third-grade students at MI Al-Barokah still faced various obstacles in reading, including spelling letters one by one, needing the teacher's help when pronouncing words, difficulty distinguishing certain letters, often repeating words or sentences, and not being able to read fluently overall. The use of puzzle media proved to be effective in helping teachers overcome these problems. The use of this media was also able to increase student activity, foster a spirit of learning, and foster their interest in reading activities in the third grade at MI Al-Barokah.